Consumption Value Theory on Purchasing Decisions for Online Halal Food - Wijayanti, Farah Nur Syafi'ah (CV. Civiliza Publishing, 2025)
Therefore, halal branding is used to reduce cognitive dissonance in Muslim consumers. The consumption market for halal products mostly consists of Asian (63 percent), Middle Eastern (23.6 percent) and European (10.5 percent) markets, it is important for the halal product industry to understand consumer purchasing behavior so that this knowledge can be used to increase halal product consumption and market performance in the future because halal products include products that are acceptable and have positive feedback so it is possible for Indonesians to buy halal products. Suggests consumption value as a variable of consumption behavior (purchase decisions, etc.), pre-consumption behavior (such as intention, search, etc.) and post-consumption behavior (such as satisfaction, repurchase, adoption, switching, and engagement). To identify the moderating effect of halal awareness on the effect of consumption value on online halal food purchase decisions. In this study there are 11 hypotheses with. Hypotheses will be tested using PLS-SEM by determining the structural model used by the statistical program. Estimation of the structural model is done by looking at the coefficient of determination (R²), predictive relevance (Q²), the size and significance of the path coefficient, and the effect size f². All tests were conducted using PLS-SEM with WarpPLS 8 as the testing software. This study has 11 hypotheses with 7 hypotheses supported and 4 not supported. The existence of time limitations is less widespread so that it can allow this to cause many hypotheses that are not supported, therefore future research can be given a longer time frame and spread more widely. For the future, it can be carried out in different halal contexts such as halal tourism, Islamic-based retail, and lodging that uses the concept of sharia using consumption value theory.